DAMPAK PABRIK SAWIT PT FAJAR BAIZURI & BROTHERS TERHADAP SOSIAL EKONOMI MASYARAKAT TADU RAYA - Wahyudi, Irham; Badli, Saiful; Tanjung, Indra Ismayudi (Universitas Teuku Umar, 2023)
This study aims to determine the impact of the existence of the palm oil processing plant (PKS) PT. Fajar Baizuri & Brothers on the socio-eco nomic community around Tadu Raya District, Nagan Raya Regency. PT. Fajar Baizuri & Brothers as one of the palm oil processing companies operating in Tadu Raya District, Nagan Raya Regency, has an important role in driving economic activity in the area. Most of the surrounding community depend on their livelihoods on activities related to the company, either as direct labor or through supporting businesses such as trade, transportation, and services. The method used in this study is a descriptive method by processing quantitative data. The sample in this study amounted to 97 people in the Tadu Raya District, Nagan Raya Regency. This study uses primary data, namely the results of respondents' questionnaire answers. The data analysis method used is the t- test difference test. The results of this study indicate that the existence of the Palm Oil Processing Plant (PKS) PT. Fajar Baizuri & Brothers has an impact on the social and economic community around Tadu Raya District, Nagan Raya Regency, with a significant value of less than 0.05 (0.000 <0.05), thus the hypothesis that the existence of the Palm Oil Processing Factory (PKS) of PT. Fajar Baizuri & Brothers has an impact on the social and economic community around Tadu Raya District, Nagan Raya Regency, is accepted.